Rapid Preparation of Manganese Monoxide by Microwave-Enhanced Selective Carbothermal Reduction - Chen, Jin; He, Fei; Gao, Lei; Guo, Shenghui; Omran, Mamdouh; Chen, Guo (Frontiers in Energy Research, 2022)
Most of the manganese resources in China have existed in the form of low-grade pyrolusite which is not utilized efficiently because of the high energy consumption and environmental pollution during the reduction process. Applying microwave heating to minerals reduction endows improved production efficiency and reduced production costs. In the present work, rapid preparation of manganese monoxide (MnO) was attempted through reducing low-grade pyrolusite with coal reducing agent by microwave heating, with the samples characterized by XRD, scanning electron microscopy, XPS as well as TG/DSC. The influences of the reduction reaction parameters on the reduction process of Mn in pyrolusite were comprehensively studied. The results indicated that higher temperatures and longer holding times facilitated the reduction roasting of pyrolusite, and manganese monoxide can be fabricated with a reduction ratio of 97.7% obtained at 650°C for 50 min. The mechanism of the gradual transformation of MnO2 to MnO from the macroscopic to the molecular level was also revealed in the order of MnO2 → Mn2O3 → Mn3O4 → MnO. Compared to traditional roasting, the proposed microwave-enhanced roasting process benefits from the superior kinetic conditions provided by the synergy between microwave enhancement and compact pellets, and thus reduced the roasting temperature and roasting time.